Relationship of Q-Angle With Walking Speed in Knee Osteoarthritis Patients - Muchammad Yahya Yahya; Firdausi Kahfi Maulana; Nur Luthfiatus Solikah (Journal of Sports Medicine and Physiotherapy, 2025)
Background: Knee Osteoarthritis is one of the biggest health problems in the world because knee Osteoarthritis is a degenerative disease whose condition severity usually increases with age. Patients with osteoarthritis of the knee often complain of various symptoms, especially pain, which can interfere with their functional activities, including walking. With age, the severity of the condition increases, potentially leading to alignment abnormalities in the knee. Alignment abnormalities occur due to changes in the Q-angle from the normal position. An increase in Q-angle occurs with malalignment, which will cause functional abnormalities and can result in subluxation of the patella and trigger various complaints in the knee.Objectives: In patients with Knee Osteoarthritis patients often complain of a variety of complaints especially pain that disrupts the functional activity of patients including the ability of the patient to walk, as the age increases the severity of the condition that the possibility of Q-angle changes will occur malalignment that will cause abnormalities of function and trigger the emergence of various complaint on the knee.Methods: The research method used in this study is a correlative descriptive method. The study was conducted over a three-day period with respondents of 38 patients diagnosed with knee osteoarthritis between the ages of 40-70 years in the ambulatory care Husada Utama Hospital Surabaya. A large measurement of the Q-Angle angle and the speed of walking using 10mFPWTResults: After measurement and statistical test using chi-square test has obtained P value of 0,000. which is value less than 0.05.Conclusion: There's a relationship" between large Q-angle and speed walking in patients with knee osteoarthritis.